2022
DOI: 10.1242/dmm.049203
|View full text |Cite
|
Sign up to set email alerts
|

AMP-activated protein kinase promotes breast cancer stemness and drug resistance

Abstract: Breast Cancer Stem Cells (BCSCs) are a major cause of therapy resistance and tumour progression. Currently, their regulation is not entirely understood. Previous work from our lab demonstrated context-specific pro-tumorigenic role of AMP-activated protein kinase (AMPK) in breast cancer cell survival under anchorage-deprivation and mammosphere formation hallmarks of BCSCs. We therefore investigated the role of AMPK in the maintenance of BCSC state/function. AMPK depletion reduces serial sphere formation in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 56 publications
(75 reference statements)
0
9
0
Order By: Relevance
“…Recent studies supported the notion that AMPK activation enhances the anticancer effects of cisplatin [ 62 , 63 ]. Nevertheless, some studies reported conflicting results on the tumor-promoting effects of AMPK activation [ 64 , 65 ]. Now, it is proposed that AMPK can behave as a CSC “friend” or “foe” in a tissue type-specific and context-dependent manner [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies supported the notion that AMPK activation enhances the anticancer effects of cisplatin [ 62 , 63 ]. Nevertheless, some studies reported conflicting results on the tumor-promoting effects of AMPK activation [ 64 , 65 ]. Now, it is proposed that AMPK can behave as a CSC “friend” or “foe” in a tissue type-specific and context-dependent manner [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, some studies reported conflicting results on the tumor-promoting effects of AMPK activation [ 64 , 65 ]. Now, it is proposed that AMPK can behave as a CSC “friend” or “foe” in a tissue type-specific and context-dependent manner [ 65 ]. The widespread use of AMPK activators should be trialed cautiously across disease settings of cancers [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…After 48 h of incubation, cells were subjected to RNA isolation as described earlier. 54 Briefly, 0.5 mL of Trizol (Sigma Aldrich) was added to the cells and then 0.2 mL of chloroform was added and centrifuged gently for the aqueous layer separation. Further, the aqueous layer was separated into the fresh tube and an equal volume of isopropanol was added to precipitate the RNA.…”
Section: Methodsmentioning
confidence: 99%
“…After, 12 h of seeding cells were treated with lipoplexes namely; ED, EC, MC, and MD, liposomes; EDL, ECL, MCL, and MDL and PBS for 24 h. After 24 h of treatment, cells were trypsinized and resuspended in a 500 μL binding buffer containing annexin‐V FITC/PI and incubated for 15 min in the dark. Then the samples were analyzed using a flow cytometer (FACS accuri, Beckton Dickinson, USA) and apoptosis was analyzed using BD‐Accuri software [48,50] …”
Section: Methodsmentioning
confidence: 99%